The role of modern women in society and family - Rustam Fayzullaev, Firuza Sadikova, Zukhra Ismailova, Dustnazar Khimmataliev Masuda Khashimova, (Opción, 2019)
The purpose of this article is to determine the extent to which working women in Uzbekistan are able to maintain this balance, as well as to formulate recommendations that can help improve the situation. Based on the goals, for the collection of information, it was decided to conduct an empirical study, which consisted of a survey of students. Purposive sampling was considered the most appropriate sampling method. As a result, the survey identified some problems that affect the balance between work and family for women. In conclusion, responsibility for the successful solution of problems lies with the women themselves.